Classroom management strategies for the English language teaching and learning process with the students of fashion design, beauty and cosmetology at “Latacunga Artisanal Educative Unit" during the academic cycle 2014-2015 - Villegas Moposita, Myrian Tatiana (2015)
This research work was focused on the students of Fashion Design, Beauty and Cosmetology at “Latacunga Artisanal Educative Unit”, which is located in Latacunga city during the academic cycle 2014-2015; which aims to improve classroom management and also the teaching-learning process of the English language through the implementation of a strategy booklet which contains interesting activities to motivate teachers and students during the teaching-learning process. This booklet is essential to facilitate and encourage the students' learning, which helped to improve the development of the four skills of the English language. In addition, this booklet facilitated the work of teachers using different activities for the students learn English in a fast and fun way….